Millennial Worker Retention Strategy; A Literature Study - Agus Sudono; Syamsul Hadi Senen; Rofi Rofaida (Budapest International Research and Critics University, 2022)
Millennial workers are known to easily change jobs, tend to be free of expression, and want fast progress in careers and competencies, they dominate with a proportion of 56.1% of the total workforce. This study aims to reveal recommendations for retention strategies for millennial workers from recent studies. The method used is a systematic literature review of journal articles published in reputable international journals from the Emerald and SAGE Journals databases. The search results identified 9 journal articles relevant to the research objectives. The results of the study show that a competitive climate that values achievement, openness to express opinions, open opportunities to pursue careers and competencies, quality mentors, and appreciation for expression creates a culture in relevant corridors are a series of strategies that are seen as able to accommodate millennial workers to develop, last longer, and improve the competitiveness of company.